Political Will Pemerintah Daerah Kabupaten Bogor Dalam Memberantas Budaya Pungli Uji KIR - Aldaffa Malik Hindarsyah; Ridwan Ridwan (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
The phenomenon of illegal levies (pungli) remains a persistent issue in Indonesia’s public service delivery, including in the vehicle roadworthiness testing process (Uji KIR). Despite more than two decades of bureaucratic reform, such practices continue to occur and are often perceived as “unofficial fees” to expedite services. This study aims to analyze the political will of the Bogor Regency Government in eradicating the culture of pungli within the Uji KIR process through three main dimensions: political commitment, policy choices, and institutional actions. This research employs a descriptive qualitative approach, utilizing primary data collected through in-depth interviews with the Regional Secretary of Bogor Regency, the Head of the Motor Vehicle Testing Division at the Department of Transportation, and a public policy analyst. Secondary data were obtained from regulations, official government reports, and academic literature. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña (2014), which includes data reduction, presentation, and conclusion drawing. The results indicate that the local government’s political will remains suboptimal. Political commitment is still normative, digitalization of services has not effectively closed bureaucratic loopholes, and internal supervision remains weak. The study concludes that eradicating pungli requires sustained political will through policy transparency, institutional reform, and enhanced public participation in oversight.